Pengaruh Intervensi Gizi Sensitif terhadap Kejadian Stunting pada Balita Usia 6-24 Bulan selama Pandemi Covid-19: Pengaruh Intervensi Gizi Sensitif terhadap Kejadian Stunting pada Balita Usia 6-24 Bulan selama Pandemi Covid-19 - Elya Sugianti; Berliana Devianti Putri (Amerta Nutrition, 2022)
Background: Stunting is still a national and global problem because of its impact on the quality of future generations. The government has launched various stunting reduction programs through nutrition-specific and sensitive interventions. However, the scope of interventions is still dominated by specific-nutrition interventions. In addition, the Covid-19 pandemic has resulted in several programs not being able to be implemented properly. Objectives: to analyze the effect of the nutrition-sensitive intervention on the incidence of stunting among toddlers aged 6-24 months during the pandemic Covid-19 Methods: This study was observational analytic with a cross-sectional design. The research was conducted in Lamongan, Sampang, and Probolinggo Regencies from June to July 2022. The sample selection used a simple random sampling technique and a total of 384 toddlers were calculated using the Cohran formula. The sample was added to 455 toddlers to avoid refusal of participation in the study. Primary data were obtained with interviews and anthropometric measurements. All research data were analyzed using the chi-square test and logistic regression Results: The results showed that the availability of adequate latrines affected the incidence of stunting among toddlers aged 6-24 months (p=0.008; OR=2.260; 95%CI: 1.238-4.125). Another variable that affects the incidence of stunting is the age of toddlers (p = 0.001; OR = 3.205; 95% CI: 1.657-6.201). Conclusions: Access to adequate latrines is a nutrition-sensitive intervention that has most influenced the incidence of stunting among toddlers aged 6-24 months during the Covid-19 pandemic.